Disabilities in Pakistan's R&D sector: knowledge management capability - Zeeshan, Asim; Surrilya, Sarwat; Sorooshian, Shahryar; Muhammad Shahid, Ahmad (International Information Institute, 2017)
Developing new knowledge capabilities provides an opportunity to create new technologies that diverts conventional business approach to R&D driven business approach, by configuring knowledge and innovation as adequate strategic asset for creating progressive balance sheet. Consistent variations in current technological trends with groundbreaking technologies help on catalyzing to boost operational productivity that open new segment of economic activities. The purpose of this research study is to review present involvement of knowledge management capabilities in practices to facilitate R&D activities in case of lower middle economics like 'Pakistan'. This study explores crucial information on existing threats that Pakistan's governmental R&D sector's confronting in context of implement knowledge management capabilities. ln support, this study identifuing some of unclear evidences on adoption of knowledge capabilities in developing economies like Pakistan, after applying extensive review on global competitive index (GCI) develop by world economic forum (WEF) and global innovation index (GII) of year 2015-2016 with respect to other regional; emerging and middle income economies.